La La land - Chazelle, Damien (Summit Entertainment, 2017)
A jazz pianist falls for an aspiring actress in Los Angeles. Struggling actress Mia (Emma Stone) and aspiring jazz pianist Sebastian (Ryan Gosling) begin a whirlwind romance as they both pursue their dreams in Los Angeles. However, their blossoming relationship is challenged when their careers pull them in different directions.